Comparative Studies Of Residual Water Level In Manado And Melonguane Coastal Area During Tropical Cyclone In 2021 - Azani, Audia Azizah; Djamaluddin, Rignolda; Bara, Robert A; Manu, Lusia; Dien, Heffry Veibert; Manembu, Indri Shelovita (Sam Ratulangi University, 2024)
North Sulawesi Province, directly bordering the Pacific Ocean, is located in an area with the highest level of tropical cyclone (TC) activity in the world. As a result, the province is vulnerable to the impacts caused by cyclones, including storm surges. The increase in water levels due to this event has the potential to cause coastal flooding. Previous studies in Manado have identified that sea level rise can be detected through residual water level (RWL), making studying the characteristics of RWL in North Sulawesi important. This research focuses on Manado and Melonguane, allowing for a comparison of characteristics. The data used includes tropical cyclone data from the China Meteorological Administration (CMA) and tidal data from the Geospatial Information Agency. The Unified Tidal Analysis and Prediction (UTide) method is used to identify RWL. The analysis was carried out by using a t-test to compare data at the two locations. The results showed that RWL at those locations had significant differences with Melonguane having the higher value between them. Generally, the increase in RWL in Melonguane occurs shortly after the cyclone period, while the RWL in Manado maximum increases 86 hours after TC's first occurrence. Keywords: tropical cyclone; residual water level; UTide.